Devotional Portraiture and Spiritual Experience in Early Netherlandish Painting | catalogue - Falque, Ingrid (Brill, 2019)
This is the first exhaustive catalogue of paintings with devotional portraits produced in the Low Countries between c. 1400 and 1550. This printed catalogue is an appendix to the book Devotional Portraiture and Spiritual Experience in Early Netherlandish Painting. The catalogue is 952 pages in size (hardcover, full-color).; Readership: All interested in the study of early Netherlandish paintings and more precisely of theirs functions and meanings, and anyone concerned with the relationships between art and spirituality in the late Middle Ages. Keywords: Early Netherlandish painting, Low Countries, 1400-1550, images, art, painting, devotion, spiritual literature, Flemish Primitives, spirituality, mysticism, Modern Devotion, iconology, late Middle Ages, art history.